Recruitment of young adult cancer survivors into a randomized controlled trial of an mHealth physical activity intervention - Valle, Carmina G.; Camp, Lindsey N.; Diamond, Molly; Nezami, Brooke T.; LaRose, Jessica Gokee; Pinto, Bernardine M.; Tate, Deborah F. (Current controlled trials in cardiovascular medicine, 2022)
Purpose Few studies have recruited young adult cancer survivors (YACS) from around the USA into remotely-delivered behavioral clinical trials. This study describes recruitment strategies used in the IMproving Physical Activity after Cancer Treatment (IMPACT) study, a 12-month randomized controlled trial of a mobile physical activity intervention for YACS. Methods We conducted formative work to guide development of recruitment messages and used a variety of methods and channels to recruit posttreatment YACS (diagnosed ages 18–39, participating in < 150 min/week of moderate-to-vigorous intensity activity). We used targeted social media advertisements, direct mailings, clinical referrals, and phone calls to potentially eligible individuals identified through local tumor registries. We also asked community organizations to share study information and advertized at a national conference for YACS. Results The final sample of 280 participants (23% identified as racial/ethnic minority individuals, 18% male, mean 33.4 ± 4.8 years) was recruited over a 14-month period. About 38% of those who completed initial screening online ( n = 684) or via telephone ( n = 63) were randomized. The top recruitment approach was unpaid social media, primarily via Facebook posts by organizations/friends (45%), while direct mail yielded 40.7% of participants. Other social media (paid advertisements, Twitter), email, clinic referrals, and conference advertisements each yielded 3% or fewer participants. The most cost-effective methods per participant recruited were unpaid social media posts and direct mailings. Conclusions The IMPACT trial successfully met enrollment goals using a national strategy to recruit physically inactive YACS. Our approaches can inform recruitment planning for other remotely-delivered intervention trials enrolling YACS. Trial registration ClinicalTrials.gov NCT03569605 . Registered on 26 June 2018.